ANALISIS DAUR HIDUP (LIFE CYCLE ASSESSMENT) PENGOLAHAN KOPI BUBUK ROBUSTA SECARA BASAH DI INDUSTRI KECIL MENENGAH (IKM) BELOE KLASIK LAMPUNG - Febilian Adiwinata; Suprihatin Suprihatin; Mulyorini Rahayuningsih (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Indonesia is one of the countries with the largest producer of coffee commodities globally. The high productivity of coffee is a good opportunity to establish Small and Medium Industries for coffee processing. The increase in coffee production will affect the quality of the environment due to the entire series of coffee production activities such as pollution or emissions and waste. The policies set by the government encourage industries to become environmentally friendly and sustainable industries. An assessment of the coffee processing life cycle needs to be carried out to determine how big the environmental impact is from the production process. The magnitude of the environmental impact can be calculated using the Life Cycle Assessment (LCA) method from providing raw materials to products ready for consumption by consumers resulting in environmental impacts and requiring energy that can be calculated. The purpose of this study is to analyze and evaluate the environmental impact of coffee processing production activities using the Life Cycle Assessment (LCA) method with a gate to gate scope. The stages of LCA research are setting research objectives and scope, inventory analysis, environmental impact assessment, and implementation of improvements. The environmental impact analyzed is Greenhouse Gas (GHG) emissions which are categorized as one of the causes of Global Warming Potential (GWP). The results of the LCA analysis show that for every one tonne of wet-processed coffee, 1900 MJ of energy will be used, and GHG emissions of 270.17 Kg CO2eq / day are equivalent to 1.31 CO2eq / kg of ground coffee, which is equivalent to 6,438 Kg CO2eq. / month and 77,260 Kg CO2eq/ year.